THE ANALYSIS OF SPEECH ACT IN A COMIC CONVERSATION - Thomas Joni Verawanto Aristo; Frederykus Ege (STKIP Persada Khatulistiwa Sintang, 2018)
The purpose of this research was to analyze speech act of comic conversation. An utterance has two kinds of meaning, they are, Proportional meaning (locutionary meaning): is a speech act that a speaker performs when referring or predicting an utterance or the literal meaning of what is said. This is basic literal meaning of the utterance which is conveyed by the particular words and structures that the utterance contain, and Illocutionary meaning (illocutionary force): the social function of what is said. This is the real meaning the speaker intends to express. There are five speech acts classification; they are, First, Representative: statements may be judged true or false because they aim to describe a state of affairs in the world. Second, Directive: statements attempt to make the other person's actions fit the propositional content. Third, Comissive: A statements that commits the speaker to doing something in the future. Then, Expressive: A statement in which the speaker expresses feeling and attitudes about something. And the last, Declarative: statements that attempt to change the world by “representing it as having been changed”. Maxims conversation is one of the instrument to develop the conversation to be good. The theory can be identified four unit, they are: Quality: make your contribution truthful and sincere, Quantity: provide sufficient information, Relation: make your contribution a relevant one, and Manner: make your contribution brief, present it in an orderly fashion and avoid ambiguisties. The focuses of this study are to describe the locutionary and ilocutionary meaning of used in the comic and to describe the speech act classification used in the comic.In this research, researcher used qualitative and the tool of data collection was used documentation. the researcher tried to analyze the data using Ethnography of communication Dell Hymes’s SPEAKING mnemonic. Keyword: Speech Act, Comic, Conversation